The Black Woman's Burden: A Discussion of Race, Rape Culture, and Feminism - Hamid, Rawabi (2020)
Current feminist and anti-rape movements in the United States seek to amplify the voices of women regarding sexual assault. Unfortunately, within this amplification, the voices of Black women are often excluded, which is a direct effect of historically ignoring the abuses of Black women and rarely ever bringing their abusers to justice. These injustices, often committed by white men and perpetuated by white women, create a destructive rhetoric in stereotyping Black women while also silencing them throughout modern movements, especially those of feminist and anti-rape causes. This essay will examine the consequences of three problematic aspects of US history and the role of these aspects in silencing Black women: first, the role of slavery and how the abuse Black women faced at the hands of white slave owners was often ignored, while resentful white women whose male relatives carried out these abuses created the stereotype of the promiscuous Black woman; second, the role of the destructive history of the rape charge and lynching in the post-Civil War era in not only over-criminalizing Black men but also creating the precedent of Black women not receiving the same justice for sexual assault and rape as their white counterparts; finally, the history of feminist and anti-rape movements in the United States and their ongoing, deliberate exclusion of Black women based on stereotypes created by white women